A Discourse Analysis Towards News Report of Jakarta Regional Election of 2017 About the Issues of Political Promises in the Campaign on Media Indonesia.com and okezone.com - Ayub Dwi Anggoro and Aziz Amin (International Journal of Advanced Science and Technology, 2020)
The independence of media is expected to provide balanced, neutral informationbecause it may greatly determine the quality of the ongoing regional election. As theopposite, there is also a possibility in which media is used as a tool to build politicalpower. That is why there is a new phenomenon in which many media owners are involvedand even actively participated in politics in Indonesia. Therefore, they emphasize more onusing online media to develop their media business. One of the advantages of using onlinemedia is that it can provide the new propaganda faster. In addition, as the media ishaving its power to build the public opinion, they got the power to directly lead thestakeholders to certain political interests. In this study, news report on MediaIndonesia.com published and okezone.com was used as the object of study in order toidentify the case of regional election in Jakarta about the Issues of Political Promises.